Toward a Nature-Centered Design - Carla Paoliello; Beike Li; Elena Metzdorf (DIID)
This conceptual paper critically examines the Human-Centered Design focus of Design Thinking and the Double Diamond methodology, highlighting their limitations in addressing global challenges. It advocates for an urgent paradigm shift toward Nature-Centered Design (NCD), a design process that prioritizes ecological sustainability and harmonious relationships with nature and non-humans, valuing nature’s wisdom over its resources and considering interconnected social, economic, and environmental factors. NCD envisions a future in which designers collaborate with non-human elements, challenging pre-settled hierarchies. It endorses a perspective, aligning the Symbiocene epoch concepts with Indigenous wisdom to foster empathy and respect for nature. In conclusion, other questions arise about society’s readiness for NCD and the transformative role of Design in shaping a sustainable future. The result is a statement about the significance of (re)connecting with nature, recognizing it as a fundamental pursuit for fostering a harmonious coexistence and cultivating a deeper understanding of the place of humans within the intricate web of life.